Efektivitas Pain Assement Tool (PAT) Pada Pasien Dengan Penurunan Kesadaran Di Ruang Intensive Care - rahmawati, choiri rahmawati; Al-Afik; Maryadi (2025)
Intensive Care Unit is a treatment room for patients in critical condition with a high risk of death, so intensive and continuous monitoring is needed. Patients in critical condition require close monitoring and intensive therapy, so it is not uncommon for patients in intensive care to experience pain. Pain assessment in the intensive care unit is challenging, especially in patients who are receiving analgo-sedatives, are unconscious, and using ventilators. The purpose of this study was to determine the effectiveness of the pain assessment tool (PAT) in patients with decreased consciousness in the intensive care unit. This study used a descriptive survey research design with a cross-sectional approach. The sample in this study was 13 respondents. The instrument used in this study was the Critical Care Pain Observation Tool (CPOT). The data analysis technique used was univariate data analysis. The results of the study showed that the majority of respondents experienced moderate pain during rest as many as 10 (76.9%) and when nursing actions were carried out severe pain as many as 8 (61.5%).